The Development of Jumping Ability in Young Handball Players 12-13 Years Old - Sitorabonu Savriddin Qizi Abduyeva (S&Co Publishing, 2023)
To increase the level of jumping ability (high-speed strength abilities), a depth jump training program has been developed, taking into account technical and tactical actions in the game